2013
DOI: 10.1111/bjh.12546
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of alleles encoding high‐ and low‐prevalence red blood cell antigens across Africa: useful data to facilitate transfusion in African patients

Abstract: Summary Ethnic variations in red blood cell (RBC) antigens can be a source of alloimmunization, especially in migrant populations. To improve transfusion safety in continental Africa and countries with African migrants, we performed RBC genotyping to determine allele frequencies coding for high‐ and low‐prevalence antigens. A total of 481 blood samples were collected in ethnic groups from West, Central and East Africa. Molecular typing was performed using a polymerase chain reaction – reverse sequence specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Our study confirmed the high frequencies of DO*JO and DO*HY alleles previously observed in people from Africa . DO*JO and DO*HY alleles were present in all of the cohorts tested, except that the DO*HY allele was absent from the South African Bantus and from the D.R.C.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study confirmed the high frequencies of DO*JO and DO*HY alleles previously observed in people from Africa . DO*JO and DO*HY alleles were present in all of the cohorts tested, except that the DO*HY allele was absent from the South African Bantus and from the D.R.C.…”
Section: Discussionsupporting
confidence: 92%
“…Given the considerable variability in allele frequencies among African populations previously reported, we found that type DO*B alleles i.e., DO*B , DO*B‐WL , DO*B‐SH , and the other DO*B variants were slightly more common among African ethnic groups than in African migrant populations (mean frequency 0.743 vs. 0.719). In sub‐Saharan cohorts, DO*B allelic diversity seemed higher than in the three migrant populations.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…S1). For CEPH DNA samples, whole genome amplification was performed and validated as previously described . While the Teke, Tswa, and San samples were used for ART4 sequencing experiments, the Ngala, Biaka, and Mbuti samples were screened for the presence of the DO*B‐SH‐Gln149Lys variant allele.…”
Section: Methodsmentioning
confidence: 99%